India in international climate governance: Through soft power from REDD to REDD+ policy in favor of relative gains - Swati Negi; Lukas Giessen (Forest and Society, 2018)
This paper seeks to examine India’s role in the politics of a specific climate change mitigation policy called “Reducing emissions from deforestation and forest degradation, and enhancing forest carbon stocks in developing countries (REDD+)”. It explores India’s strategic behaviour towards the development of REDD policy. The paper argues that India had pushed for the remodelling of the global REDD negotiations by expanding its scope to conservation activities, which entails more direct benefits for India. This is largely due to differences in India’s rates of forest cover and deforestation as compared to high forest - high deforestation countries such as Brazil and Indonesia. To substantiate its argument, the paper uses the main underpinnings of relative gains theory in international relations and applies them toward interpreting India’s behaviour in negotiating REDD+ at global level. Further, the paper analyses the Indian strategies used to remodel the REDD mechanism using insights from soft power theory and its more recent amendments. Thematic analysis of the REDD-relevant documents as well as exploratory expert interviews have been employed for showing India’s proactive role in the politics of REDD+. It is concluded that India indeed played a central role in critical past decisions, which lead to re-shaping REDD due to relative gains concerns and mainly by means of soft power strategies.